SISTEM E-FILLING: KEPATUHAN WAJIB PAJAK ORANG PRIBADI STUDI KASUS PADA PT. POLAPULPINDO MANTAP - Supriatiningsih Supriatiningsih; Veronica Melinda Astrinigsih (STIE Muhammadiyah Jakarta, 2020)
The change to the regulations of taxes often confuse tax payers with assessable or taxable properties. The relatively underprivileged capacity of their understanding about tax regulation related to these from time-to-time changes itself, igniting the unexpected level of ignoring or even apathetic attitude, which can inhibit required obedience in paying taxes. In this research, we interested in studying deeply about perceived of ebilling and efillingy and influence towards compliance of taxpayer personality at PT. Monysaga Prima. Perceive can be branchmarking whether the tax payers understand the problems, and tax payers perceiving towards those regulations of income taxes with respect to can raise tax payers compliance. By utilizing samples of respondents, that is 68 tax payers registered at PT. Monysaga prima, this research examines the effect of perceived of ebilling and efillingy towards compliance of taxpayers. This statistical method used is multiple regression analysis with SPSS. The result of analysis indicated that confidence level 95% (sig 5%) which means that there are effect of ebillingg and efilling its has significan result